2020
DOI: 10.1111/gcb.15445
|View full text |Cite
|
Sign up to set email alerts
|

Climate‐driven carry‐over effects negatively influence population growth rate in a food‐caching boreal passerine

Abstract: Understanding how events throughout the annual cycle are linked is important for predicting variation in individual fitness, but whether and how carry‐over effects scale up to influence population dynamics is poorly understood. Using 38 years of demographic data from Algonquin Provincial Park, Ontario, and a full annual cycle integrated population model, we examined the influence of environmental conditions and density on the population growth rate of Canada jays (Perisoreus canadensis), a resident boreal pass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 33 publications
0
21
1
Order By: Relevance
“…It is interesting that jay productivity trended upward from 2018 to 2019, given the unusually warm temperatures and lack of snowpack during our autumn 2018 and spring 2019 field seasons. Previous studies examining the influence of freeze-thaw events have found a negative correlation with fecundity (Sutton et al 2019;Sutton et al 2021). Of course, our observations were not of multiple freeze thaw events, but rather delays or accelerations of seasonal temperature and snowpack changes.…”
Section: Discussioncontrasting
confidence: 40%
“…It is interesting that jay productivity trended upward from 2018 to 2019, given the unusually warm temperatures and lack of snowpack during our autumn 2018 and spring 2019 field seasons. Previous studies examining the influence of freeze-thaw events have found a negative correlation with fecundity (Sutton et al 2019;Sutton et al 2021). Of course, our observations were not of multiple freeze thaw events, but rather delays or accelerations of seasonal temperature and snowpack changes.…”
Section: Discussioncontrasting
confidence: 40%
“…Notwithstanding this putative protection of cached food, the Algonquin study population has decreased by more than 50% since the 1970s (Waite and Strickland 2006;Strickland et al 2011;Sutton et al 2021). There has been no detected change in forest composition over this same time period, but correlational and experimental evidence supports the hypothesis that this decline has been caused by increases in fall temperatures (Waite and Strickland 2006) and/or an increase in the number of freeze-thaw events (Sutton et al 2019).…”
Section: Introductionmentioning
confidence: 76%
“…There has been no detected change in forest composition over this same time period, but correlational and experimental evidence supports the hypothesis that this decline has been caused by increases in fall temperatures (Waite and Strickland 2006) and/or an increase in the number of freeze-thaw events (Sutton et al 2019). These climatic changes likely accelerate the degradation of cached food (Sechley et al 2015), leading to lower-than-average reproductive success (Waite and Strickland 2006;Sutton et al 2019) and negative population growth rates (Sutton et al 2021). The general finding from the Algonquin Park studies is that the preservation of perishable food stores and hence the demographic fortunes of the park's range-edge Canada jays, benefit from the antimicrobial properties of spruce spp.…”
Section: Introductionmentioning
confidence: 99%
“…In APP, an individually marked population of Canada jays located along the APP's highway 60 corridor has been monitored since 1964 with data on reproductive performance and survival collected annually (Fig. 1; Rutter 1969, Strickland and Waite 2001, Derbyshire et al 2015, Sutton et al 2021a). The study area covers an east-west distance of approximately 55 km and extended a maximum distance of 8 km north or south of the highway 60 corridor.…”
Section: Study Area and Focal Speciesmentioning
confidence: 99%
“…Being perishable, food cached by Canada jays is susceptible to degradation over time, especially when exposed to warm temperatures during normally belowfreezing periods (Sutton et al 2019). This degradation of perishable cached food causes Canada jays to experience lower reproductive success when the fall and winter preceding the breeding season has had warmer temperatures and/or more freeze-thaw events than normal (Waite and Strickland 2006, Sutton et al 2019, 2021a.…”
Section: Introductionmentioning
confidence: 99%